2019
DOI: 10.1371/journal.pone.0221492
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and molecular genotyping of Salmonella enterica serovar Enteritidis clinical isolates from Guizhou province of Southwestern China

Abstract: Salmonella enterica serovar Enteritidis (S. Enteritidis) is the most common and essential serotype that causes salmonellosis in Guizhou province. This study aimed to investigate the antimicrobial resistance (AMR) and molecular genotyping of 79 S. Enteritidis clinical isolates from 2011 to 2016 in Guizhou, China. Antimicrobial resistance and minimum inhibitory concentrations (MICs) of S. Enteritidis clinical isolates were detected by micro broth dilution method against ten classes 16 antimicrobial agents, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The antimicrobial resistance of all Salmonella isolates was examined using previously reported the method of micro broth dilution (Xingbai, Shanghai) [ 1 ]. Sixteen antimicrobial agents of ten classes were tested, including Penicillin (ampicillin), Phenicols (chloramphenicol), Aminoglycosides (streptomycin, gentamicin), Carbapenems (imipenem), β-lactamase inhibitor (amoxicillin/clavulanic acid), Cephems (cefoxitin, ceftriaxone, cefepime), Sulfonamides (sulfamethoxazole, trimethoprim-sulfamethoxazole), Tetracyclines (tetracycline, doxycycline), Quinolones and Fluoroquinolones (nalidixic acid, ciprofloxacin), Macrolides (azithromycin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial resistance of all Salmonella isolates was examined using previously reported the method of micro broth dilution (Xingbai, Shanghai) [ 1 ]. Sixteen antimicrobial agents of ten classes were tested, including Penicillin (ampicillin), Phenicols (chloramphenicol), Aminoglycosides (streptomycin, gentamicin), Carbapenems (imipenem), β-lactamase inhibitor (amoxicillin/clavulanic acid), Cephems (cefoxitin, ceftriaxone, cefepime), Sulfonamides (sulfamethoxazole, trimethoprim-sulfamethoxazole), Tetracyclines (tetracycline, doxycycline), Quinolones and Fluoroquinolones (nalidixic acid, ciprofloxacin), Macrolides (azithromycin).…”
Section: Methodsmentioning
confidence: 99%
“…Salmonella is one of the most common pathogens of infectious diarrhea worldwide [ 1 ]. It is an essential foodborne and zoonotic pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the high priority given to Salmonella in the context of food safety and antimicrobial resistance. Our previous surveillance results have shown that food-related disease cases in Guizhou Province are mostly caused by Salmonella typhimurium ( Wei et al, 2019 ; Bai et al, 2022 ; Long et al, 2022 ; Wei et al, 2023 ). Concerningly, we also have recently reported a foodborne outbreak in Guizhou caused by Salmonella ( Zhou et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…resistance to at least two classes of antimicrobials) in S . Enteritidis varied greatly from different regions and countries as well: 2.2% in the U.S. 4 , 3.2% in Europe 6 , 42% in sub-Saharan Africa 5 , and 40–81% in China 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%